Data from: breeding under pressure: corticosterone is associated with reproductive investment under fluctuating predation risk in a long-lived sea duck - Mohring, Bertille; Öst, Markus; Jaatinen, Kim; Parenteau, Charline; Grimaud, Emmanuelle; Angelier, Frédéric (Zenodo, 2023)
Phenotypic plasticity may enable individuals to cope with predictable and unpredictable environments during their life-cycle. In that context, studying glucocorticoids – corticosterone (CORT) in birds – is relevant because of their primary role in allostasis. Higher baseline CORT levels are classically associated with environmental constraints and lower fitness (the CORT-fitness hypothesis). However, in some environments, higher baseline CORT levels can promote reproduction, therefore being associated with higher fitness (the CORT-adaptation hypothesis). These two hypotheses have been tested in multiple systems, but rarely in a context of fluctuating predation threat. We used a long-term individual-based monitoring of baseline CORT levels in female common eiders Somateria mollissima (n CORT = 1537; n individual = 790; 2009-2022) to disentangle the context-dependent links between environmental conditions, CORT and fitness. Importantly, the study population has been facing a drastic increase in predation pressure over the past decades, linked to the recovery of the white-tailed eagle Haliaeetus albicilla . Additionally, eiders breed on open or forested islands, further affecting adult and nest predation risk. This system allowed us to disentangle the relative contributions of within- and among-individual variation in baseline CORT levels under predation. Supporting the CORT-adaptation hypothesis, baseline CORT levels were positively associated with reproductive investment (clutch size), age and hatching success. By partitioning within- and among-individual effects, we showed that at the individual level, CORT flexibly increased with clutch size and age. Females displaying higher CORT levels were more successful, suggesting a link between CORT and individual quality. At both the population and individual levels, baseline CORT levels decreased over the study period. This decrease was correlated with an increase in predation risk. Females had reduced baseline CORT when nesting under high eagle abundance or adult ...